Preparation of Cerium Modified Titanium Dioxide Nanoparticles and Investigation of Their Visible Light Photocatalytic Performance - Jinfeng Liu; Haiyan Li; Qiuye Li; Xiaodong Wang; Min Zhang; Jianjun Yang (International Journal of Photoenergy)
Mesoporous CeOx/TiO2 nanoparticles have been successfully synthesized using titanate nanotubes as precursor through the hydrothermal-calcination method. The as-prepared materials were characterized by means of X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM), UV-vis diffuse reflectance spectra and nitrogen adsorption-desorption isotherm analysis. All the obtained CeOx/TiO2 materials exhibit anatase phase. Ce element existed in two valance states of Ce3+ and Ce4+. Introduction of Ce species can effectively extend the spectral response from UV to visible light region. N2 adsorption-desorption analysis revealed that all the samples belong to mesoporous structure and have large BET surface area compared with P25. The CeOx/TiO2 nanoparticles showed excellent photocatalytic activity in the degradation of MB under visible light irradiation.